-3(x-2)+4(x-7)=20

Simple and best practice solution for -3(x-2)+4(x-7)=20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-2)+4(x-7)=20 equation:


Simplifying
-3(x + -2) + 4(x + -7) = 20

Reorder the terms:
-3(-2 + x) + 4(x + -7) = 20
(-2 * -3 + x * -3) + 4(x + -7) = 20
(6 + -3x) + 4(x + -7) = 20

Reorder the terms:
6 + -3x + 4(-7 + x) = 20
6 + -3x + (-7 * 4 + x * 4) = 20
6 + -3x + (-28 + 4x) = 20

Reorder the terms:
6 + -28 + -3x + 4x = 20

Combine like terms: 6 + -28 = -22
-22 + -3x + 4x = 20

Combine like terms: -3x + 4x = 1x
-22 + 1x = 20

Solving
-22 + 1x = 20

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + 1x = 20 + 22

Combine like terms: -22 + 22 = 0
0 + 1x = 20 + 22
1x = 20 + 22

Combine like terms: 20 + 22 = 42
1x = 42

Divide each side by '1'.
x = 42

Simplifying
x = 42

See similar equations:

| u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t | | 4*(x+6)= | | X(-2)+18=50(-3x)+25 | | 2*(x+3)= | | 2*(3a)= | | -24+x=36 | | (-2x)+5+3x+-4x+(-1)+(-x)= | | 2x+(-2)=17 | | 6*2s=39 | | ×/3-4=×/5-6 | | 2(-1)+y=17 | | Y+12=c | | 3/7=n/21 | | 4.5+x=-2.3 | | 10x-15=6x+14 | | 3(7+2x)=7(x-1) | | ln(5-x)=2.3 | | 7m-2t=72 | | (5+23x-3)-5=13x+20(-3) | | 15+-3x= | | 231m*j=123851 | | 3/8=n/24 | | 11j+7j=-48 | | 3/4-1/3=1/6 | | 7y+7-y=10+5y+6 | | x+.05x=40530 |

Equations solver categories